PELATIHAN KEWIRAUSAHAAN PEMBUATAN MINUMAN THAI TEA DAN PERHITUNGAN HARGA POKOK PRODUKSI PADA IBU-IBU PKK RT 2 RW 5 PERUMAHAN MUARA SARANA INDAH JETIS MULYOAGUNG DAU MALANG - Indrayati Indrayati; Ludfi Djajanto; Basuki Rachmat; Kuni Utami; Suryadi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
Entrepreneurship Training in making Thai Tea and calculation of the cost of production is one of the efforts to provide knowledge for PKK mothers to improve nutrition or endurance as well as increase income for PKK mothers in Muara Sarana Indah housing Mulyoagung Dau Malang. This effort to improve nutrition is the responsibility of universities, especially Malang State Polytechnic in order to increase endurance by making their own processed food at a lower cost. This PKM was carried out on August 14 and 15, 2021.